(untitled) (Progressive Agriculture, 2020)
In Bangladesh, the cost of building materials is increasing gradually, available raw materials of construction are not sufficient to meet up the needs of the country. For that we have to find out cheaper and waste materials (such as ceramic waste) to reuse for construction. The study was conducted to observe the physical properties of waste ceramics and compressive strength of ceramics mortar for different curing ages. The study was done to check the probability of using waste ceramics instead of natural aggregates (sand).The fineness modulus of ceramics aggregates was 2.94. Ceramic aggregate absorbs 5.89% moisture whereas sand absorbs 14.33%. Generally, finer the aggregate shows greater the compressive strength. Though the fineness modulus of ceramics was greater than that of sand, it possessed higher compressive strength because of its self-strength. The ratio of mortar mixture was (1:2) and (1:3) for different curing periods both sand and ceramics samples. The compressive strength of sand and ceramic mortar was 2603 psi and 3500 psi respectively at the ratio of (1:2) for 3 days curing. On the other hand the compressive strength of sand and ceramics mortar was 2340 psi and 3075 psi respectively at the ratio of (1:3) for 3 days curing. Between the sand and ceramic mortar, the compressive strength of ceramic mortar was found maximum at 28 days curing period. It can be concluded that recycled ceramic aggregates will be used in comparatively low load bearing, low cost temporary and medium category farming etc. concrete structure. Progressive Agriculture 30 (3): 311-316, 2019